No Commonality in Liquidity on Small Emerging Markets? Evidence from the Central and Eastern European Stock Exchanges - Joanna Olbrys\' (Comparative Economic Research. Central and Eastern Europe, 2020)
The goal ofthis comparative research isto investigate intra-market commonality inliquid-ity onsix small emerging Central and Eastern European (CEE) stock exchanges - inthe Czech Republic, Hungary, Slovakia, Lithuania, Estonia, and Latvia. The CEE post-commu-nist countries can beanalyzed together asthey are geographically close, and the stock markets are relatively similar. Three measures based ondaily data are utilized asliquidity/illiquidity proxies: (1) amodified version ofthe Amihud (2002) measure, (2) the percentage relative spread, and (3) the Corwin-Schultz (2012) high-low two-day spread estimator. The OLS regression with the HAC covariance matrix estimation and the GARCH-type models are employed toexplore the patterns ofmarket-wide commonality inliquidity onthe CEE stock exchanges. The main value-added comes from the methodology and the novel empirical findings. Tothe best ofthe author's knowledge, this isthe first study that investigates commonality inliquidity inthe aforementioned group ofcountries using three liquidity proxies and the time rolling-window approach toprovide robustness tests. The regressions reveal nopronounced evidence ofco-movements inliquidity within the CEE markets, taken separately. What isimportant, the empirical results are homogeneous for all investigated markets. Therefore, noreason has been found toreject the research hypothesis that there isno commonality inliquidity oneach individual market. This paper aspires tofill the gap inthe knowledge ofliquidity patterns onthe CEE emerging markets.
Keywords: C32; C58; G12; G15; O52; 330; Central and Eastern Europe; commonality inliquidity; GARCH; OLS-HAC; time rolling-window; daily data